Method for producing plated coating film

By forming an electrolytic nickel plating film with controlled compressive stress and subsequent trivalent chromium plating, the method addresses corrosion and gloss issues in conventional plating films, achieving enhanced resistance and appearance for industrial uses.

CN119183481APending Publication Date: 2024-12-24OKUNO CHEM IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380040253.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-19
Filing Date
2023-03-30
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Conventional trivalent chromium plating films suffer from inferior corrosion resistance and microcracks, while hexavalent chromium plating films exhibit fine microcracks, and both are inadequate in terms of glossiness for applications requiring hardness and wear resistance.

Method used

A method involving the formation of an electrolytic nickel plating film with a compressive stress of 0 to 100 MPa, followed by an electrolytic trivalent chromium plating film, with specific roughness, hardness, and thickness conditions, to create a multilayer structure that suppresses crack formation and enhances corrosion resistance and gloss.

Benefits of technology

The method produces a trivalent chromium plated film with excellent corrosion resistance and gloss, suitable for industrial applications by suppressing crack formation and improving wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132143570000051
    Figure BDA0005132143570000051
  • Figure BDA0005132143570000151
    Figure BDA0005132143570000151
  • Figure BDA0005132143570000171
    Figure BDA0005132143570000171
Patent Text Reader

Abstract

The technical problem to be solved by the present invention is to provide a method for producing a plated film, which is capable of imparting excellent corrosion resistance to an object to be plated on which a trivalent chromium plated film has been formed, and which is capable of forming a trivalent chromium plated film having excellent glossiness. The present invention provides a method for producing a plating film, the method being characterized by comprising: a step 1 for forming an electrolytic nickel plating film; and a step 2 for forming an electrolytic trivalent chromium plating film on the electrolytic nickel plating film. The compressive stress of the electrolytic nickel plating film is 0-100 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a plating film. Background Art

[0002] Conventionally, hard chrome plating, which has properties such as hardness and wear resistance, has been widely used for automobile parts, molding dies, calendar rolls, printing rolls, and the like.

[0003] A trivalent chromium plating solution and a trivalent chromium plating method for performing chromium plating have been proposed (see Patent Document 1).

[0004] However, the plated film formed by the trivalent chromium plating bath is prone to cracks that penetrate the substrate. On the other hand, the plated film formed by the hexavalent chromium plating bath generates fine microcracks in the film. Therefore, the hard trivalent chromium plating film has a problem of inferior corrosion resistance compared to the hexavalent chromium plating.

[0005] In addition, since chromium plating is used for the above-mentioned purposes, glossiness is required. Therefore, there is a need for a method for producing a plating film that can form a trivalent chromium plating film having excellent corrosion resistance and glossiness.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2006-249518 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] An object of the present invention is to provide a method for producing a plated film, which can impart excellent corrosion resistance to an object to be plated on which a trivalent chromium plated film is formed, and can form a trivalent chromium plated film having excellent gloss.

[0011] Solutions for solving technical problems

[0012] The inventors of the present invention have repeatedly conducted in-depth research and found that the above-mentioned purpose can be achieved by adopting the following method for manufacturing a plated film, thereby completing the present invention. The above-mentioned method for manufacturing a plated film includes: step 1 of forming an electrolytic nickel plated film; and step 2 of forming an electrolytic trivalent chromium plated film on the electrolytic nickel plated film, and the electrodeposition stress of the above-mentioned electrolytic nickel plated film is a compressive stress, and the compressive stress is within a specific range.

[0013] That is, the present invention relates to the following method for producing a plated film.

[0014] 1. A method for manufacturing a plating film, comprising:

[0015] Step 1 of forming an electrolytic nickel plating film; and

[0016] Step 2 of forming an electrolytic trivalent chromium plating film on the electrolytic nickel plating film,

[0017] The compressive stress of the electrolytic nickel plating film is 0 to 100 MPa.

[0018] 2. The production method according to item 1, wherein the electrolytic trivalent chromium plating film has an arithmetic mean roughness Ra of 0.080 μm or less.

[0019] 3. The production method according to item 1 or 2, wherein the thickness of the electrolytic trivalent chromium plating film is 2 μm or more.

[0020] 4. The production method according to any one of items 1 to 3, wherein the electrolytic trivalent chromium plating film has a Vickers hardness of 750 HV or more.

[0021] 5. The production method according to any one of items 1 to 4, wherein the step 2 is a step of intermittently forming an electrolytic trivalent chromium plating film.

[0022] Effects of the Invention

[0023] The method for producing a plated film of the present invention can impart excellent corrosion resistance to an object to be plated on which a trivalent chromium plated film is formed, and can produce a trivalent chromium plated film having excellent gloss. DETAILED DESCRIPTION

[0024] The manufacturing method of the plated film of the present invention is characterized in that it includes: step 1 of forming an electrolytic nickel plated film; and step 2 of forming an electrolytic trivalent chromium plated film on the electrolytic nickel plated film, and the compressive stress of the electrolytic nickel plated film is 0 to 100 MPa. In the manufacturing method of the present invention, the electrodeposition stress of the electrolytic nickel plated film of the substrate is a compressive stress, and the compressive stress is 0 to 100 MPa. Therefore, by making the electrodeposition stress of the electrolytic trivalent chromium plated film tensile stress, the electrodeposition stress is relaxed, the occurrence of cracks is suppressed, and excellent corrosion resistance can be given to the plated object formed with the trivalent chromium plated film. In addition, by adopting the manufacturing method of the present invention, by suppressing the occurrence of cracks in the plated film as described above, an electrolytic trivalent chromium plated film with excellent gloss can be manufactured. That is, the manufacturing method of the present invention includes the above-mentioned steps 1 and 2, and the compressive stress of the electrolytic nickel plating film is 0 to 100 MPa, so that excellent corrosion resistance can be imparted to the plated object formed with the electrolytic trivalent chromium plating film, and an electrolytic trivalent chromium plating film with excellent gloss can be manufactured.

[0025] (Process 1)

[0026] Step 1 is a step of forming an electrolytic nickel plating film.

[0027] The electrolytic nickel plating solution used to form the electrolytic nickel plated film is not particularly limited as long as it can make the compressive stress 0 to 100 MPa. As such an electrolytic nickel plating solution, specifically, a so-called Watts Bath containing nickel sulfate, nickel chloride, boric acid, etc., an aminosulfonic acid nickel bath containing nickel sulfamate, a so-called impact plating bath (Wood Bath: Wood Bath) containing nickel chloride, etc. can be listed. In addition, various nickel baths containing nickel monohydroxide, nickel carbonate and nickel acetate, etc. can also be used. In the manufacturing method of the present invention, as the electrolytic nickel plating solution, a Watts bath and an aminosulfonic acid bath are preferred. From the perspective of further improving the wear resistance of the plated film manufactured by the manufacturing method of the present invention, an aminosulfonic acid bath is more preferred.

[0028] As the electrolytic nickel plating solution, specifically, an electrolytic nickel plating solution containing a water-soluble nickel compound can be used. In addition, a primary brightener, a secondary brightener, a potential regulator, an anti-dent agent, etc. can be added to the electrolytic nickel plating solution.

[0029] (Water-soluble nickel compounds)

[0030] As a water-soluble nickel compound, there is no particular limitation as long as it is soluble in water. As such a water-soluble nickel compound, nickel sulfate, nickel chloride, nickel sulfamate, nickel carbonate and their hydrates can be listed. As a water-soluble nickel compound, more specifically, nickel sulfate hexahydrate, nickel chloride hexahydrate, nickel sulfamate, nickel carbonate tetrahydrate and the like can be listed. Among these, nickel sulfamate, nickel chloride and their hydrates are preferably used, and a mixture of nickel sulfamate and nickel chloride or its hydrate is more preferably used, from the perspective of being able to more easily adjust the compressive stress of the electrolytic nickel plating film to 0-100MPa, further suppressing the occurrence of cracks, and giving a more excellent corrosion resistance to the plated object formed with the trivalent chromium plating film.

[0031] The above-mentioned water-soluble nickel compounds may be used alone or in combination of two or more.

[0032] The content of nickel sulfamate and its hydrate in the electrolytic nickel plating solution is preferably 200 to 500 g / L, more preferably 220 to 400 g / L, and even more preferably 230 to 350 g / L. By making the content of nickel sulfamate and its hydrate within the above range, the compressive stress of the electrolytic nickel plating film can be more easily adjusted to 0 to 100 MPa, the occurrence of cracks can be further suppressed, and the plated object formed with the trivalent chromium plating film can be given more excellent corrosion resistance.

[0033] The content of nickel sulfate and its hydrate in the electrolytic nickel plating solution is preferably 200 to 500 g / L, more preferably 220 to 400 g / L, and even more preferably 230 to 350 g / L. By setting the upper limit of the content of nickel sulfate and its hydrate to the above range, the occurrence of depressions due to the increase in the specific gravity of the plating solution can be further suppressed. By setting the lower limit of the content of nickel sulfate and its hydrate to the above range, the occurrence of white fog and burning in the appearance of the plated film can be further suppressed.

[0034] The content of nickel chloride and its hydrate in the electrolytic nickel plating solution is preferably 30 to 70 g / L, more preferably 35 to 60 g / L, and even more preferably 40 to 55 g / L. By making the content of nickel chloride and its hydrate within the above range, the compressive stress of the electrolytic nickel plating film can be more easily adjusted to 0 to 100 MPa, the occurrence of cracks can be further suppressed, and the plated object formed with the trivalent chromium plating film can be given more excellent corrosion resistance.

[0035] (Primary brightener)

[0036] The electrolytic nickel plating solution preferably contains a primary brightener. By making the electrolytic nickel plating solution contain a primary brightener, the compressive stress of the electrolytic nickel plating film can be more easily adjusted to 0 to 100 MPa.

[0037] As the primary brightener, sulfur compounds, sulfonic acid compounds, etc. can be used. Sulfur compounds are preferred because they can more easily adjust the compressive stress of the electrolytic nickel plating film to 0 to 100 MPa, further suppress the occurrence of cracks, and provide more excellent corrosion resistance to the plated object formed with the trivalent chromium plating film.

[0038] Examples of the sulfur-based compound include heterocyclic compounds containing sulfur and nitrogen as heteroatoms, sulfur-containing heterocyclic compounds, etc. Among these, heterocyclic compounds containing sulfur and nitrogen as heteroatoms and sulfur-containing heterocyclic compounds are preferred, and heterocyclic compounds containing sulfur and nitrogen as heteroatoms are more preferred, from the viewpoint of being able to more easily adjust the compressive stress of the electrolytic nickel plating film to 0 to 100 MPa, further suppressing the occurrence of cracks, and imparting more excellent corrosion resistance to the plated object formed with the trivalent chromium plating film.

[0039] As the primary brightener, a heterocyclic compound represented by the following general formula (1) is preferred.

[0040]

[0041] By using the heterocyclic compound represented by the general formula (1) as the primary brightener, the compressive stress of the electrolytic nickel plating film can be more easily adjusted to 0 to 100 MPa, the occurrence of cracks can be further suppressed, and more excellent corrosion resistance can be imparted to the plated object formed with the trivalent chromium plating film.

[0042] In the above general formula (1), R 1 It is S or SO 2. Among these, SO 2 is preferred from the viewpoints of being able to more easily adjust the compressive stress of the electrolytic nickel plating film to 0 to 100 MPa, further suppressing the occurrence of cracks, and imparting more excellent corrosion resistance to the plated object formed with the trivalent chromium plating film.

[0043] In the above general formula (1), R 2 H, Cl, Br, I or CH 3. Among these, H or CH 3 is preferred from the viewpoints of being able to more easily adjust the compressive stress of the electrolytic nickel plating film to 0 to 100 MPa, further suppressing the occurrence of cracks, and imparting more excellent corrosion resistance to the plated object formed with the trivalent chromium plating film.

[0044] More specifically, the primary brightener includes 1,2-benzisothiazol-3(2H)-one, saccharin, N-methyl saccharin, N-chloro saccharin, N-bromo saccharin, and N-iodo saccharin. Among these, 1,2-benzisothiazol-3(2H)-one, saccharin, N-methyl saccharin, and N-chloro saccharin are preferred, and 1,2-benzisothiazol-3(2H)-one, saccharin, and N-methyl saccharin are more preferred, because the compressive stress of the electrolytic nickel plating film can be more easily adjusted to 0 to 100 MPa, the occurrence of cracks can be further suppressed, and a more excellent corrosion resistance can be imparted to the plated object formed with the trivalent chromium plating film.

[0045] The above primary brighteners may be used alone or in combination of two or more.

[0046] The content of the primary brightener in the electrolytic nickel plating solution is preferably 0.1 to 10 g / L, more preferably 0.2 to 5 g / L, and even more preferably 0.2 to 2 g / L. By setting the lower limit of the content of the primary brightener to the above range, the compressive stress of the electrolytic nickel plating film can be more easily adjusted to 0 to 100 MPa, the occurrence of cracks can be further suppressed, and the plated object formed with the trivalent chromium plating film can be given more excellent corrosion resistance. By setting the upper limit of the content of the primary brightener to the above range, the sulfur content of the glossy nickel plating film is suppressed, and the reduction of corrosion resistance is further suppressed.

[0047] (Secondary Brightener)

[0048] The electrolytic nickel plating solution preferably contains a secondary brightener. When the electrolytic nickel plating solution contains a secondary brightener, the surface of the electrolytic nickel plating film becomes smoother, and the glossiness of the trivalent chromium plating film formed in step 2 is further improved.

[0049] As the secondary brightener, carbon-multiple bond compounds, carbon-heteroatom multiple bond compounds, etc. Carbon-multiple bond compounds are preferred from the viewpoint of making the surface of the electrolytic nickel plating film smoother and further improving the glossiness of the trivalent chromium plating film formed in step 2.

[0050] Examples of the secondary brightener include unsaturated compounds having a double bond and / or a triple bond between carbons, etc. Among these, unsaturated compounds having a triple bond between carbons are preferred from the viewpoint of making the surface of the electrolytic nickel plating film smoother and further improving the glossiness of the trivalent chromium plating film formed in step 2.

[0051] Preferred secondary brighteners include sodium propargylsulfonate, butynediol diethoxy compounds, hexynediol, unsaturated compounds represented by the following general formula (2), and unsaturated compounds represented by the following general formula (3).

[0052] R 3 -R 4 -C≡C-CH2-OH (2)

[0053] R 5 -C≡C-CH2-OH (3)

[0054] By using these unsaturated compounds as the secondary brightener, the surface of the electrolytic nickel plating film becomes smoother, and the glossiness of the trivalent chromium plating film formed in step 2 is further improved.

[0055] In the above general formulas (2) and (3), R 3 and R 5 In order to make the surface of the electrolytic nickel plating film smoother and to further improve the glossiness of the trivalent chromium plating film formed in step 2, the above R 3 and R 5 Preferred is H or CH3.

[0056] In the above general formula (2), R 4 The above R is an alkyl group having 1 to 7 carbon atoms or a propargyl group. In order to make the surface of the electrolytic nickel plating film smoother and to further improve the glossiness of the trivalent chromium plating film formed in step 2, 4 Preferably, R 4 The number of carbon atoms in is preferably 1-5, more preferably 1-3.

[0057] More specifically, the secondary brightener includes 2-propyn-1-ol (propargyl alcohol), sodium propynyl sulfonate, sodium propylene sulfonate, 1,4-butynediol, 2-butyn-1-ol, 2-pentyn-1-ol, butynediol diethoxylate, 2-hexyn-1-ol, hexynediol, 2-heptyn-1-ol, 2-octyne-1-ol, 2-nonyn-1-ol, 2-decyn-1-ol, and 2,4-hexadiyn-1,6-diol. Among these, 2-propyn-1-ol (propargyl alcohol), 1,4-butynediol, 2-butyn-1-ol, butynediol diethoxylate, and hexynediol are preferred from the viewpoint of making the surface of the electrolytic nickel plating film smoother and further improving the glossiness of the trivalent chromium plating film formed in step 2.

[0058] The secondary brighteners may be used alone or in combination of two or more.

[0059] The content of the secondary brightener in the electrolytic nickel plating solution is preferably 0.005 to 3 g / L, more preferably 0.02 to 1.8 g / L, and more preferably 0.04 to 1.5 g / L. By setting the lower limit of the content of the secondary brightener to the above range, the surface of the electrolytic nickel plating film becomes smoother, and the glossiness of the electrolytic trivalent chromium plating film formed in step 2 is further improved.

[0060] (Potential Regulator)

[0061] The electrolytic nickel plating solution preferably contains a potential adjuster. By making the electrolytic nickel plating solution contain a potential adjuster, the potential of the electrolytic nickel plating film can be set to a higher potential, and the corrosion resistance of the electrolytic nickel plating film can be improved.

[0062] As the potential regulator, for example, aldehyde compounds, diol compounds, etc. can be used. Among these, diol compounds are preferred from the viewpoints of being able to further increase the carbon content of the electrolytic nickel plating film, further reduce the sulfur content, thereby further improving the corrosion resistance of the electrolytic nickel plating film, and being able to set the potential of the electrolytic nickel plating film to a higher potential.

[0063] Preferred potential adjusters include aldehyde compounds represented by the following general formula (4), aldehyde compounds represented by the following general formula (5), diol compounds represented by the following general formula (6), and diol compounds represented by the following general formula (7).

[0064] R 6 -R 7 -CHO (4)

[0065] R 8 1 CHO (5)

[0066] R 9 -R 10-CH(OH)2 (6)

[0067] R 11 -CH(OH)2 (7)

[0068] By using the aldehyde compounds represented by the general formulae (4) and (5) and the diol compounds represented by the general formulae (6) and (7) as potential adjusters, the corrosion resistance of the electrolytic nickel plating film can be further improved.

[0069] In the above general formulas (4) to (7), R 6 , R 8 , R 9 and R 11 It is H, Cl, Br, CH 3 , CBr 3 or CCl 3 . Among these, H, CH 3 , Cl and CCl 3 are preferred from the perspective of further improving the corrosion resistance of the electrolytic nickel plating film.

[0070] In the above general formulas (4) and (6), R 7 and R 10 is an alkyl group having 1 to 7 carbon atoms or a vinyl group. In order to further improve the corrosion resistance of the glossy nickel plating film, the above R 7 and R 10 Preferably, R 7 and R 10 The number of carbon atoms in is preferably 1-5, more preferably 1-3.

[0071] As the potential regulator, more specifically, acetaldehyde, formaldehyde, propionaldehyde, butyraldehyde, hexanal, 3-chloropropionaldehyde, chloroacetaldehyde, chloral hydrate, bromoaldehyde hydrate, 3-methylbutyraldehyde, 2-propenal and 2-butenal can be cited. Among these, chloroacetaldehyde, chloral hydrate, 2-propenal and 2-butenal are preferred from the perspective of being able to further improve the corrosion resistance of the electrolytic nickel plating film.

[0072] The above-mentioned potential adjusting agents may be used alone or in combination of two or more.

[0073] The content of the potential regulator in the electrolytic nickel plating solution is preferably 0.001 to 1 g / L, more preferably 0.002 to 0.1 g / L, and more preferably 0.005 to 0.05 g / L. By making the content of the potential regulator within the above range, the carbon content of the electrolytic nickel plating film can be further increased, and the sulfur content can be further reduced to further improve the corrosion resistance of the electrolytic nickel plating film, and the potential of the electrolytic nickel plating film can be set to a higher potential.

[0074] (Other additives)

[0075] The electrolytic nickel plating solution preferably contains the water-soluble nickel compound described above, and if necessary, contains the primary brightener, secondary brightener, and potential adjuster described above, and is more preferably an aqueous solution containing these.

[0076] The electrolytic nickel plating solution may contain an anti-recessing agent, a pH buffering agent, and the like in addition to the above-mentioned components.

[0077] Examples of the anti-dent agent include surfactants such as nonionic surfactants, anionic surfactants, and cationic surfactants. The content of the anti-dent agent is not particularly limited, and can be, for example, about 0.01 to 10 g / L.

[0078] Examples of the pH buffer include boric acid, phosphoric acid, phosphorous acid, carbonic acid, and sodium salts, potassium salts, and ammonium salts thereof. The amount of the pH buffer to be added is not particularly limited, and can be, for example, about 0.1 to 200 g / L.

[0079] The pH of the electrolytic nickel plating solution may be generally about 3.5 to 5.0, preferably about 3.8 to 4.8. Inorganic acids such as sulfuric acid and hydrochloric acid; metal carbonates such as nickel carbonate; sodium hydroxide; ammonia water, etc. may be used to adjust the pH.

[0080] When the electrolytic nickel plating is performed using the electrolytic nickel plating solution, the electrolytic nickel plating solution is brought into contact with the object to be plated according to a conventional method. Usually, the object to be plated is immersed in the electrolytic nickel plating solution and electrolytic plating is performed, thereby efficiently forming an electrolytic nickel plating film.

[0081] The liquid temperature of the electrolytic nickel plating solution may be generally about 45 to 65° C., preferably about 50 to 60° C. In addition, the plating solution may be stirred or the object to be plated may be shaken as necessary.

[0082] The current density during electrolytic nickel plating is set to 1 to 6 A / dm 2 It is about 2-4A / dm. 2 about.

[0083] The plating time may be appropriately determined according to the target film thickness of the electrolytic nickel plating film, and may be about 10 to 30 minutes.

[0084] The material of the object to be plated is not particularly limited as long as it can be electrolytically plated, and examples thereof include metals such as iron, copper, zinc, and aluminum, alloys thereof, and resins subjected to base plating.

[0085] In the manufacturing method of the present invention, the electrodeposition stress of the electrolytic nickel plating film formed by step 1 is a compressive stress. That is, the compressive stress of the electrolytic nickel plating film is 0 to 100 MPa. When the compressive stress is lower than 0 MPa, it becomes a tensile stress, and the electrodeposition stress of the trivalent chromium plating film formed in the later-described step 2 is also a tensile stress. Therefore, the electrodeposition stress cannot be relaxed, and the occurrence of cracks cannot be suppressed. Therefore, it is impossible to impart excellent corrosion resistance to the plated object formed with the trivalent chromium plating film. When the compressive stress exceeds 100 MPa, cracks are easily generated in the nickel plating film, and the corrosion resistance of the trivalent chromium plating film is poor. The compressive stress of the electrolytic nickel plating film is preferably 0 to 50 MPa.

[0086] In this specification, the compressive stress of the electrolytic nickel plating film can be measured by the method described in the Examples described later.

[0087] The arithmetic mean roughness Ra of the electrolytic nickel plated film is preferably 0.080 μm or less, more preferably 0.050 μm or less, and even more preferably 0.040 μm or less. By setting the upper limit of the arithmetic mean roughness Ra to the above range, the glossiness of the electrolytic trivalent chromium plated film formed on the electrolytic nickel plated film by the step 2 described later is further improved. In addition, the lower limit of the arithmetic mean roughness Ra can be lower, for example, it can be about 0.020 μm.

[0088] In this specification, the arithmetic mean roughness Ra of the electrolytic nickel plating film can be measured according to the measurement method specified in JIS B0601-2001.

[0089] The Vickers hardness of the electrolytic nickel plated film is preferably 300 HV or more, more preferably 350 HV or more, and more preferably 400 HV or more. In addition, the Vickers hardness of the electrolytic nickel plated film is preferably 1000 HV or less, more preferably 900 HV or less, and more preferably 800 HV or less. By making the range of the Vickers hardness within the above range, the occurrence of cracks in the plated film manufactured by the manufacturing method of the present invention is further suppressed, and the corrosion resistance is further improved.

[0090] In this specification, the Vickers hardness of the electrolytic nickel plating film is measured by the measurement method specified in JIS Z2244-1:2020.

[0091] The thickness of the electrolytic nickel plated film is preferably 5 μm or more, more preferably 10 μm or more. In addition, the thickness of the electrolytic nickel plated film is preferably 50 μm or less, more preferably 30 μm or less. By making the thickness of the electrolytic nickel plated film within the above range, the electrolytic trivalent chromium plated film formed on the electrolytic nickel plated film by the step 2 described later is tensile stress, so that the occurrence of cracks in the plated film is further suppressed, and the corrosion resistance of the plated film is further improved.

[0092] (Process 2)

[0093] Step 2 is a step of forming an electrolytic trivalent chromium plating film on the electrolytic nickel plating film.

[0094] The electrolytic trivalent chromium plating solution for forming the electrolytic trivalent chromium plating film is not particularly limited, and a conventionally known electrolytic trivalent chromium plating solution can be used.

[0095] As the electrolytic trivalent chromium plating solution, for example, an electrolytic trivalent chromium plating solution containing a trivalent chromium compound, a complexing agent, a conductive salt, and a pH buffer can be used.

[0096] (Trivalent chromium compounds)

[0097] The trivalent chromium compound may be any water-soluble trivalent chromium compound, and for example, chromium sulfate, chromium chloride, basic chromium sulfate, etc. The trivalent chromium compound may be used alone or in combination of two or more.

[0098] The concentration of the trivalent chromium compound in the electrolytic trivalent chromium plating solution is not particularly limited, but is preferably about 20 to 60 g / L, more preferably about 30 to 45 g / L, in terms of chromium metal concentration, for example.

[0099] (Complexing agent)

[0100] The complexing agent is not particularly limited as long as it is a compound having a complexing ability with trivalent chromium, but it is preferred to use at least one compound selected from water-soluble aliphatic carboxylic acids and salts thereof.

[0101] There is no particular limitation on the type of water-soluble aliphatic carboxylic acid, as long as it is a carboxylic acid that can form an aqueous solution of a predetermined concentration. For example, aliphatic monocarboxylic acids such as formic acid, acetic acid, and glycine; aliphatic dicarboxylic acids such as oxalic acid, malonic acid, and succinic acid; aliphatic hydroxymonocarboxylic acids such as gluconic acid; aliphatic hydroxydicarboxylic acids such as malic acid; aliphatic hydroxytricarboxylic acids such as citric acid, etc. can be used.

[0102] The water-soluble aliphatic carboxylic acid salt may be any water-soluble salt of the above-mentioned various carboxylic acids, and for example, alkali metal salts such as sodium salts and potassium salts, alkaline earth metal salts such as calcium salts and magnesium salts, and ammonium salts can be used.

[0103] The complexing agent may be used alone or in combination of two or more.

[0104] The amount of the complexing agent used is preferably about 0.1 to 0.8 mol per mol of trivalent chromium ions contained in the electrolytic trivalent chromium plating solution, and particularly about 0.1 to 0.3 mol per mol of trivalent chromium ions, which can increase the deposition rate of the electrolytic trivalent chromium plating film.

[0105] (Conductive Salt)

[0106] As the conductive salt, for example, sulfates such as potassium sulfate, sodium sulfate, and ammonium sulfate; chloride salts such as potassium chloride, sodium chloride, and ammonium chloride; bromide salts such as potassium bromide, sodium bromide, and ammonium bromide can be used. Among these, sulfates such as potassium sulfate, sodium sulfate, and ammonium sulfate are preferably used.

[0107] The conductive salt may be used alone or in combination of two or more.

[0108] The concentration of the conductive salt in the electrolytic trivalent chromium plating solution is not particularly limited, but is preferably about 50 to 200 g / L, and more preferably about 70 to 180 g / L.

[0109] (pH buffer)

[0110] As the pH buffer, for example, aluminum sulfate, boric acid, sodium borate, potassium borate, boric acid compounds such as boron oxide, etc. can be used. From the perspective of further improving the precipitation of the plating film in the low current density region and further improving the throwing power, it is preferred to use both aluminum sulfate and boric acid compounds.

[0111] The pH buffering agent may be used alone or in combination of two or more.

[0112] The concentration of aluminum sulfate in the electrolytic trivalent chromium plating solution is preferably 10 to 50 g / L, more preferably 20 to 40 g / L.

[0113] The concentration of the boric acid compound in the electrolytic trivalent chromium plating solution is preferably 10 to 80 g / L, more preferably 20 to 60 g / L.

[0114] The electrolytic trivalent chromium plating solution preferably contains the above-mentioned trivalent chromium compound, a complexing agent, a conductive salt, and a pH buffer, and is more preferably an aqueous solution containing these.

[0115] The pH of the electrolytic trivalent chromium plating solution is usually preferably 1.0 to 3.0, and more preferably 1.5 to 2.5. When the pH is within the above range, the precipitation property in the low current density region can be further improved, and the throwing power can be further improved.

[0116] The electrolytic trivalent chromium plating method is not particularly limited, and the same method as a general electrolytic trivalent chromium plating method may be employed using the above-mentioned electrolytic trivalent chromium plating solution.

[0117] The anode used in electrolytic trivalent chromium plating is not particularly limited, and a known insoluble anode such as a Ti-Pt electrode can be used. In particular, the use of a Ti electrode coated with an Ir-Ta composite oxide thin film is advantageous in that the generation of hexavalent chromium can be suppressed.

[0118] Regarding the temperature of the electrolytic trivalent chromium plating solution, there is a tendency that the leveling property is improved when the bath temperature is low during the plating operation, and conversely, the leveling property for low current density is reduced when the bath temperature is high. In addition, when the bath temperature is too low, there is a concern that crystallization will occur. Considering this point, the bath temperature is preferably set to about 25 to 50°C, and more preferably to about 30 to 40°C.

[0119] The current density during electrolytic trivalent chromium plating is preferably 5 to 40 A / dm 2 , more preferably 10 to 20 A / dm 2 .

[0120] The plating time may be appropriately determined according to the target film thickness of the electrolytic trivalent chromium plating film, and may be about 10 to 90 minutes.

[0121] In the manufacturing method of the present invention, the tensile stress of the electrolytic trivalent chromium plating film formed in step 2 is preferably 0 to 50 MPa, and more preferably 0 to 30 MPa. By making the electrodeposition stress of the electrolytic trivalent chromium plating film tensile stress and making the tensile stress within the above range, the electrodeposition stress of the electrolytic nickel plating film formed in the above step 1 is compressive stress, so that the electrodeposition stress is further relaxed, the occurrence of cracks is further suppressed, and more excellent corrosion resistance can be imparted to the plated object formed with the trivalent chromium plating film.

[0122] In this specification, the tensile stress of the electrolytic trivalent chromium plating film can be measured by the method described in the Examples described later.

[0123] The arithmetic mean roughness Ra of the electrolytic trivalent chromium plating film is preferably 0.080 μm or less, more preferably 0.050 μm or less, and even more preferably 0.040 μm or less. By setting the upper limit of the arithmetic mean roughness Ra to the above range, the glossiness of the electrolytic trivalent chromium plating film is further improved, and the wear resistance of the electrolytic trivalent chromium plating film is improved. In addition, the lower limit of the arithmetic mean roughness Ra can be lower, for example, it can be about 0.020 μm.

[0124] In this specification, the arithmetic mean roughness Ra of the electrolytic trivalent chromium plating film can be measured according to the measurement method specified in JIS B0601-2001.

[0125] The Vickers hardness of the electrolytic trivalent chromium plating film is preferably 750 HV or more, more preferably 800 HV or more, and even more preferably 850 HV or more. In addition, the Vickers hardness of the electrolytic trivalent chromium plating film is preferably 1500 HV or less, more preferably 1300 HV or less, and even more preferably 1200 HV or less. By making the range of the Vickers hardness within the above range, the occurrence of cracks in the electrolytic trivalent chromium plating film is further suppressed, and the corrosion resistance of the plating film is further improved.

[0126] In this specification, the Vickers hardness of the electrolytic trivalent chromium plating film is measured by the measurement method specified in JIS Z2244-1:2020.

[0127] The thickness of the electrolytic trivalent chromium plating film is preferably 2 μm or more, more preferably 5 μm or more. In addition, the thickness of the electrolytic trivalent chromium plating film is preferably 200 μm or less, more preferably 100 μm or less. By setting the thickness of the electrolytic trivalent chromium plating film to the above range, the electrolytic nickel plating film formed by the above step 1 is a compressive stress, so that the occurrence of cracks in the plating film is further suppressed, and the corrosion resistance of the plating film is further improved.

[0128] The above-mentioned step 2 may be a step of intermittently forming an electrolytic trivalent chromium plating film. By making step 2 such a step, the electrolytic trivalent chromium plating film becomes a multilayer structure, and cracks occurring on the lower side (electrolytic nickel plating film side) of the electrolytic trivalent chromium plating film can be suppressed from reaching the upper side, and the corrosion resistance of the trivalent chromium plating film is further improved.

[0129] Examples of the method for intermittently forming the electrolytic trivalent chromium plating film include a method of repeating a cycle of (1) energizing, (2) stopping electrolysis, and (3) washing with water, or a method of repeating a cycle of (1) and (2) or a cycle of (1) to (3).

[0130] The conditions of (1) to (3) above can be appropriately set according to the film thickness of the target electrolytic trivalent chromium plating film. For example, the power-on time of the above (1) is preferably 5 to 20 minutes, and more preferably 10 to 15 minutes. When repeating the cycle of (1) and (2), it is preferred to perform (1) immediately after stopping the electrolysis of (2). The electrolysis stop time of (2) is preferably within 60 seconds. In addition, the water washing process of (3) above can also be performed immediately after stopping the electrolysis of (2). The water washing time of the above (3) water washing is preferably 5 to 60 seconds, and more preferably 10 to 20 seconds.

[0131] (Heat Treatment)

[0132] In the manufacturing method of the present invention, heat treatment may be performed after the above step 2. By performing heat treatment, hydrogen embrittlement that may be generated by hydrogen adsorption in the manufactured plating film can be further suppressed. The heat treatment temperature is not particularly limited, but is preferably 100 to 500° C., more preferably 100 to 200° C. The heat treatment time is preferably 15 minutes to 180 minutes, more preferably 30 to 60 minutes.

[0133] (Articles with plated film)

[0134] The plated film produced by the production method of the present invention can be used for various purposes such as industrial chrome plating. In particular, the production method of the present invention can impart excellent corrosion resistance to the plated object formed with the trivalent chromium plated film, and can produce a trivalent chromium plated film with excellent gloss. Therefore, the plated film produced by the production method of the present invention is particularly suitable for industrial chrome plating.

[0135] Industrial chromium plating is used in various industrial fields, for example, in the production of molds, calender rolls, printing rolls, etc., by utilizing the high hardness, wear resistance, corrosion resistance, adhesion, and mold release properties of the chromium-plated film. In industrial chromium plating, metal raw materials such as steel, stainless steel, brass, and zinc die-castings are mainly used as the plated objects.

[0136] Example

[0137] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples, but the present invention is not limited to the Examples.

[0138] As an object to be plated, an iron plate (6 cm×5 cm, thickness 0.3 mm) was prepared.

[0139] [Process 1]

[0140] Each component having the following formulation was added to water in order and mixed to prepare a matte nickel plating bath (Watt bath).

[0141] (Composition of matte nickel plating bath (Watt bath))

[0142] Nickel sulfate hexahydrate: 280g / L

[0143] Nickel chloride hexahydrate: 45g / L

[0144] Boric acid: 40g / L

[0145] Additives: Add the additives shown in Table 1 as shown in Table 2.

[0146] The respective components having the following formulation were added to water in order and mixed to prepare a nickel sulfamate plating bath.

[0147] (Ni-sulfamate plating bath composition)

[0148] Nickel sulfamate: 300g / L

[0149] Nickel chloride hexahydrate: 10g / L

[0150] Boric acid: 40g / L

[0151] Additives: Add the additives shown in Table 1 as shown in Table 2.

[0152] The nickel plating additives used in the above-mentioned Watts bath and sulfamate nickel plating bath are shown in Table 1 below.

[0153] [Table 1]

[0154]

[0155] As shown in Table 2, a nickel plating bath was prepared using the base baths of the Watt bath and the aminosulfonic acid bath, and a brightener, and a nickel plating film was formed under the following nickel plating electrolysis conditions.

[0156] (Nickel plating electrolysis conditions)

[0157] pH: 4.2

[0158] Bath temperature: 55°C

[0159] Cathode current density: 3A / dm 2

[0160] Electrolysis time: 20 minutes

[0161] Film thickness (target): 10 μm

[0162] Anode: Nickel plate

[0163] Stirring: Air stirring (1L / min)

[0164] (Electrodeposition stress measurement of nickel plating film)

[0165] A nickel film was formed under the above nickel plating electrolytic conditions, and a test strip (manufactured by Fuji Chemical Co., Ltd.) was used with an effective area of ​​0.077 dm 2 The electrodeposition stress was measured under the measurement conditions of . The electrodeposition stress was calculated based on the following formula.

[0166] Electrodeposition stress (MPa) = 58.2 × UK / T

[0167] U = opening width (mm), K = coefficient (K = 0.2949 for tensile stress, K = 0.1918 for compressive stress) T = film thickness (μm) (calculated from the weight difference of the test piece before and after plating)

[0168] Table 2 shows the measured electrodeposition stress of the nickel plating film.

[0169] [Process 2]

[0170] Each component having the following blend was added to water in order to prepare a chromium plating bath (Top Fine Chrom SP-A manufactured by Okuno Chemical Industries, Ltd.).

[0171] (Chrome plating bath composition)

[0172] Top Fine Chrom SP-A Conc(Cr 3+ Source, complexing agent): 330ml / L (Cr 3+ 40g / L)

[0173] Top Fine Chrom SP-A Conductor 1 (conductive salt): 90g / L

[0174] Top Fine Chrom SP-A Conductor 2 (conductive salt): 90g / L

[0175] Top Fine Chrom SP-A Base 1 (pH buffer): 30g / L

[0176] Top Fine Chrom SP-A Base 2 (pH buffer): 40g / L

[0177] On the nickel plating film formed in the above step 1, a trivalent chromium plating film is formed using the above chromium plating bath according to the following chromium plating electrolysis conditions to produce a plated film. (Chromium plating electrolysis conditions)

[0178] pH: 1.7

[0179] Bath temperature: 35°C

[0180] Cathode current density: 15A / dm 2

[0181] Electrolysis time: 60 minutes

[0182] Film thickness (target): 8μm

[0183] Anode: Iridium oxide anode

[0184] Stirring: Air stirring (0.1L / min)

[0185] When the chromium plating film was intermittently formed, the intermittent plating was performed under the following conditions.

[0186] ·After every 10 minutes of power on, stop electrolysis and wash with water for 10 seconds

[0187] (Measurement of surface roughness Ra after chromium plating film formation)

[0188] The arithmetic mean roughness Ra (μm) of the trivalent chromium plating film side of the plating film produced in the above-mentioned steps 1 and 2 was measured by a measuring method in accordance with JIS B0601-2001.

[0189] Table 2 shows the measured arithmetic mean roughness Ra (μm) of the trivalent chromium plating film side of the plating film.

[0190] (Salt spray test)

[0191] A plated film is produced on the plated object by the above steps 1 and 2. The plated film is subjected to a salt spray test according to the measurement method of JIS Z 2371 under the measurement conditions of 35° C., 95% humidity, and 200 hours, and is evaluated according to the following evaluation criteria. In addition, when the evaluation is △ or above, it is evaluated as having no problem in practical use.

[0192] ○: No red rust occurred.

[0193] ○△: Red rust slightly occurs.

[0194] △: Red rust occurred in several places.

[0195] ×: Red rust occurred on almost the entire surface.

[0196] [Table 2]

[0197]

[0198] (Abrasion resistance test)

[0199] The plated films produced in Example 3 and Comparative Example 3 were subjected to a wear resistance test according to the reciprocating motion wear test method specified in JIS H8503 under the following measurement conditions. 500 reciprocations were counted as the number of tests per test, and the number of tests until the chromium plated film was confirmed to be peeled off was measured, and the evaluation was performed. For comparison, as Reference Example 1, a trivalent chromium plated film was directly formed on an iron plate without forming a nickel plated film, and this was also evaluated.

[0200] · Equipment: Suga abrasion tester NUS-ISO-3

[0201] Abrasive paper: #600

[0202] Load: 500gf

[0203] Number of round trips: 500

[0204] (Abrasion measurement)

[0205] The weight of the plated object with the plated film formed thereon was measured before and after the abrasion resistance test, and the weight after the abrasion resistance test was subtracted from the weight before the abrasion resistance test, and the difference was taken as the wear amount. The abrasion resistance test was performed three times on the same part, and the wear amount was measured, and the average value was taken as the measured value.

[0206] The results are shown in Table 3.

[0207] [Table 3]

[0208]

[0209] From the results in Table 3, it can be seen that the plated film of Example 3 having a nickel plated film formed by an aminosulfonic acid bath as a base has a chromium plated film with excellent wear resistance compared to the plated film of Comparative Example 3 having a nickel plated film formed by a Watt bath (semi-gloss) as a base. This is considered to be due to the low electrodeposition stress of the nickel plated film in the plated film of Example 3. In addition, it can be seen that the plated film of Example 3 has a smaller surface roughness and higher smoothness than the plated film of Comparative Example 3, and therefore, the amount of wear is also small.

Claims

1. A method for producing a plating film, characterized in that: include: Step 1 of forming an electrolytic nickel plating film; and Step 2 of forming an electrolytic trivalent chromium plating film on the electrolytic nickel plating film, The compressive stress of the electrolytic nickel plating film is 0 to 100 MPa. The tensile stress of the electrolytic trivalent chromium plating film is 0 to 50 MPa. The thickness of the electrolytic trivalent chromium plating film is 5 μm or more.

2. The manufacturing method according to claim 1, characterized in that: The electrolytic trivalent chromium plating film has an arithmetic mean roughness Ra of 0.080 μm or less.

3. The manufacturing method according to claim 1 or 2, characterized in that: The thickness of the electrolytic trivalent chromium plating film is 200 μm or less.

4. The manufacturing method according to claim 1 or 2, characterized in that: The electrolytic trivalent chromium plating film has a Vickers hardness of 750 HV or more.

5. The manufacturing method according to claim 1 or 2, characterized in that: The step 2 is a step of intermittently forming an electrolytic trivalent chromium plating film.

6. The manufacturing method according to claim 1 or 2, characterized in that: The thickness of the electrolytic nickel plating film is 5 μm or more and 50 μm or less.

Citation Information

Patent Citations

  • Method for supplying chromium ion to trivalent chromium plating bath

    JP2006249518A

  • Chrome-plated part and manufacturing method of the same

    CN102317504A

  • Nickel-chromium-plated steel band for battery steel shell

    CN102873935A

  • High corrosion resistance nano nickel and crack-free micro hard chrome composite plating layer electroplate liquid and electroplated layer manufacturing technology

    CN103451695A

  • Method for preparing trivalent chromium electroplating coating on surface of steel

    CN106906496A